ANALYSIS OF WORKING DISCIPLINE ON EMPLOYEE PERFORMANCE IN CV JACKPOT PANCING SURABAYA - Sabililah, Al Maida; Kurniawati, Rohmah (Sekolah tinggi ilmu ekonomi pemuda, 2023)
This research takes the title: Analysis of Work Discipline on Employee Performance at CV Jakcpot Pancing Surabaya. This study includes two variables, namely the work discipline variable and the employee performance variable. The research method used is descriptive qualitative method, in order to identify, explain, describe or describe and explore data based on facts found in the field based on the results of interviews, direct observation, and documentation at the research location. This research was conducted at CV Jackpot Pancing Surabaya by selecting 30 people as representative respondents, and 2 HRD Managers and GA Managers as key respondents. The data collection techniques used in this research are in-depth interviews, observation and literature study. From the results of the discussion regarding the analysis of Work Discipline on Employee Performance at CV Jackpot Pancing Surabaya, it shows that the work discipline provided by the company CV Jackpot Pancing Surabaya can improve employee performance.